SÓZI XALÍQ JÚREGINDE SAQLANǴAN ULLÍ SHAYÍR - Bekbergenova, M.D. (SCIENCE and SOCIETY, 2025)
The article analyzes the harmony of themes and ideas in the lyrical work of the poet Ajinyoza, and the artistic world of his works. The poet's work reveals a variety of topics and his skill in choosing a topic. Opinions were also expressed on the importance of scientific works and monographs on the writer’s work, on the process of study in the modern period.